2008
DOI: 10.1373/clinchem.2007.090464
|View full text |Cite
|
Sign up to set email alerts
|

High Diagnostic Accuracy of Antigen Microarray for Sensitive Detection of Hepatitis C Virus Infection

Abstract: Background: Hepatitis C virus (HCV) can be transmitted through blood transfusion. Screening ELISA, the most widely used method for HCV diagnosis, sometimes yields false-positive and false-negative results, so a confirmatory test is used. This secondary testing is labor-intensive and expensive, and thus is impractical for massive blood bank screening. Therefore, a new massive screening method with high accuracy is needed for sensitive and specific detection of HCV. Methods: With sol-gel material,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…A comparison with the 2-dimensional microarray system showed that sol-gel can immobilize proteins with a broad range up to milligram level with high activity (Kim et al, 2006;Kwon et al, 2008). Therefore, the sol-gel-integrated protein microarray appears to be ideal for measuring affinity, because sol-gel can house proteins with different concentration ranges.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison with the 2-dimensional microarray system showed that sol-gel can immobilize proteins with a broad range up to milligram level with high activity (Kim et al, 2006;Kwon et al, 2008). Therefore, the sol-gel-integrated protein microarray appears to be ideal for measuring affinity, because sol-gel can house proteins with different concentration ranges.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when the volume of the clinical samples is limited and an increasing number of pathogens per sample needs to be tested, the detecting system should be high-throughput to allow detection of multiple pathogens simultaneously [6,20,21]. Multiple detection, easy to use, and affordability are requirements for detection methods in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…HCV can be transmitted through blood transfusion. Screening ELISA, the most widely used method for HCV diagnosis, sometimes yields false-positive and false-negative results, hence Kwon and co researchers developed a high diagnostic accuracy of antigen microarray for sensitive detection of hepatitis C virus infection and their method yielded significantly fewer false-positive results and the detection limit was reported to be 1000 times more sensitive than that of the ELISA and concluded that thus developed in expensive method will improve the specificity and sensitivity of large sample volume [43] . Ciccaglione and co-researchers [44] observed that microarray analysis created a common set of cellular genes modulated by different HCV replicon clones.…”
Section: Viral Diseases (Rna Viruses)mentioning
confidence: 99%